Infliximab use and cervical spine deformity in patients with rheumatoid arthritis - Tom W J Huizinga; Rania A Mekary; Carmen L A Vleggeert-Lankamp; Anna Baukje Lebouille-Veldman (RMD Open)
Objective Over the past decades, the incidence of surgery for rheumatoid arthritis (RA)-associated cervical spine deformity decreased. Infliximab has been observed as a protective treatment for joint damage in hands and feet; yet, the protective association between infliximab and the cervical spine has been uncertain.Methods Duration of infliximab use during 10 years of follow-up was evaluated in patients with new-onset RA (case control study using data from the BeSt Trial). Missing values on the exposure were imputed using last observation carried forward. Lateral X-rays at 5-year and 10-year follow-ups were assessed for atlantoaxial subluxation (AAS) and subaxial subluxation (SAS). Multiple logistic regression models adjusted for age, gender, baseline Disease Activity Score (DAS44), ACPA-positivity and rheumatoid factor-positivity were used to estimate ORs and their 95% CIs. Mediation analysis was performed to evaluate whether a potential association was mediated via mean DAS44.Results Cervical deformity (AAS and/or SAS>2 mm) was observed in 108 (40%) of 272 patients. There was an 11% reduction in odds for cervical spine deformity (OR: 0.89, 95% CI: 0.81 to 0.98; p=0.02) for every 1-year increase in duration of infliximab use. Mediation analysis could not reveal an influence of DAS44 on the association between infliximab use and cervical spine outcomes.Conclusions There was evidence of a beneficial association between longer duration of use of infliximab and cervical spine deformity after 10 years follow-up. Thus, it is important to balance the favourable effects of infliximab use for the joints and possibly the cervical spine with the potential adverse events of this medication when used continuously.Trial registration number Netherlands Trial Register Number: NTR262.